Sinister intertextualities between literature and cinema: Mad doctors, femmes fatales, Doppelgängers and body mutilations - Santamaria Blasco, Lourdes (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Freud´ s essay The Uncanny (1919), created to analyze E. T. A. Hoffmann´ s tale The Sandman (1817), is a review of Schelling´ s concept about The Sinister, defined by the philosopher in "everything that should have remained hidden, but has finally come to ligth". Psychoanalysis converts the sinister Freudian into an aesthetic category that allows us to analyze the most disturbing part of art: the monstrous, the abject, the grotesque, the formless, the obscene, the ominous, the horrifying, etc. Sinister factors are manifested in the following literary works and films analyzed: The Island of Dr. Moreau (H. G. Wells 1895) / Island of Lost Souls (E. C. Keaton, 1932): Suddenly, Last Summer (T. Williams, 1958) / Suddenly, Last Summer (J. L. Mankiewicz, 1959); The eyes without a face (J. Redon, 1959) / Les yeux sans visage (G. Franju, 1960), and The Strange Case of Doctor Jekyll and Mister Hyde (R. L. Stevenson, 1886) / Doctr Jekyll and Sister Hyde (R. W. Baker, 1971). They include intertextualities between literature, philosophy, psychoanalysis, cinema, the chronicle of real events, the most chilling experiments of sciencie, and even comics. And its protagonists are incarnations of the sinister factor: crazy scientists, femmes fatales, Doppelgängers and body mutilations.